Bank-firm relationships, financing and firm performance in Germany - Agarwal,Rajshree; Elston,Julie (Economic Letters, 2001)
Close bank”firm relationships that characterize the financial systems in Germany and Japan are often credited for reducing agency costs and increasing access to capital, thus improving the performance of firms. Critics of these banking systems cite the alternative possibility that conflicts of interests may also arise from both the banks' multiple roles with the firm, and the opportunity the banks have to use private information to shift risk or to otherwise participate in rent-seeking activities. We extend the empirical literature by systematically investigating the impact of bank-influence on the financing choices and performance of the firm. We find that bank-influenced firms in Germany do benefit from increased access to capital. There is, however, no evidence to support the hypothesis of either higher profitability or growth for bank-influenced firms. Results suggest that the interest payments to debt ratio is significantly higher for bank-influenced firms, which supports the hypothesis that German universal banks may engage in rent-seeking activities and provides evidence of a conflicting interests between creditors and shareholders.
Keywords: Finance; OSU-Cascades